Successful resuscitation in diabetic ketoacidosis: a strong case for the use of bicarbonate. Issue 585 (July 1974) - Soler, N. G.; FitzGerald, M. G.; Bennett, M. A.; Malins, J. M.
Abstract : Although severe acidosis is a life-threatening condition owing to its cerebral and cardiac effects, correction of the acidosis with alkali remains a controversial issue in diabetic ketoacidosis. A 22-year-old female patient in diabetic ketoacidosis who was successfully resuscitated after cardiac arrest is presented and a strong case is made for the administration of bicarbonate in severe cases of diabetic ketoacidosis.